Complexity and monetary policy - Athanasios Orphanides; Volker Wieland (Goethe University Frankfurt, Center for Financial Studies (CFS), 2012)
The complexity resulting from intertwined uncertainties regarding model misspecification and mismeasurement of the state of the economy defines the monetary policy landscape. Using the euro area as laboratory this paper explores the design of robust policy guides aiming to maintain stability in the economy while recognizing this complexity. We document substantial output gap mismeasurement and make use of a new model data base to capture the evolution of model specification. A simple interest rate rule is employed to interpret ECB policy since 1999. An evaluation of alternative policy rules across 11 models of the euro area confirms the fragility of policy analysis optimized for any specific model and shows the merits of model averaging in policy design. Interestingly, a simple difference rule with the same coefficients on inflation and output growth as the one used to interpret ECB policy is quite robust as long as it responds to current outcomes of these variables.
urn:nbn:de:hebis:30:3-272544
Keywords: E50; E52; E58; 330; Financial Crisis; Complexity; Monetary Policy; Model Uncertainty; Robust Simple Rules; ECB; Geldpolitik; Regelgebundene Politik; Komplexe Systeme; Modellierung; Risiko; Schätzung; Eurozone